Neutropenia induced in outbred mice by a simplified low-dose cyclophosphamide regimen: characterization and applicability to diverse experimental models of infectious diseases (2006)
ABSTRACT: Background For its low cost and ease of handling, the mouse remains the preferred experimental animal for preclinical tests. To avoid the interaction of the animal immune system, in vivo antibiotic pharmacodynamic studies often employ cyclophosphamide (CPM) to induce neutropenia. Although high doses (350–450 mg/kg) are still used and their effects on mouse leukocytes have been described, a lower dose (250 mg/kg) is widely preferred today, but the characteristics and applicability of this approach in outbred mice have not been determined. Methods Fifteen female ICR mice were injected intraperitoneally with 150 and 100 mg/kg of CPM on days 1 and 4, respectively. Blood samples (~160 μL) were drawn from the retro-orbital sinus of each mouse on days 1, 4, 5, 6, 7 and 11. Leukocytes were counted manually and the number of granulocytes was based on microscopic examination of Wright-stained smears. The impact of neutropenia induced by this method was then determined with a variety of pathogens in three different murine models of human infections: pneumonia (Klebsiella pneumoniae, Streptococcus pneumoniae, Staphylococcus aureus), meningoencephalitis (S. pneumoniae), and the thigh model (S. aureus, Escherichia coli, Bacteroides fragilis). Results The basal count of leukocytes was within the normal range for outbred mice. On day 4, there was an 84% reduction in total white blood cells, and by day 5 the leukopenia reached its nadir (370 ± 84 cells/mm3). Profound neutropenia (≤10 neutrophils/mm3) was demonstrated at day 4 and persisted through days 5 and 6. Lymphocytes and monocytes had a 92% and 96% decline between days 1 and 5, respectively. Leukocytes recovered completely by day 11. Mice immunosupressed under this protocol displayed clinical and microbiological patterns of progressive and lethal infectious diseases after inoculation in different organs with diverse human pathogens. Conclusion A CPM total dose of 250 mg/kg is sufficient to induce profound and sustained neutropenia (<10 neutrophils/mm3) at least during 3 days in outbred mice, is simpler than previously described methods, and allows successful induction of infection in a variety of experimental models.